Spremembe ekonomskega dejavnika in varnost v sodobnem svetu - Kotnik-Dvojmoč, Igor (Teorija in praksa, 2000)
There are two important global economic changes, which decisively influence the political and security circumstances in the contemporary world. The first is a new structure of economic power, in which we can differentiate between a geopolitical (the changing of the global economic gravitation center) and an institutional aspect (the decline of the importance of the national state). The second change is substantial cuts in the field of global defence expenditures. In the most developed industrial states they are connected with the changed priorities in the process of using the reduced financial founds. Besides we should not forget the most developed industrial states are overarmed. This problem can be solved just throughout a relatively lasting and comprehensive conversion process of military capacities.
Keywords: economy; gospodarstvo; ekonomski razvoj; obrambna politika; vojaški izdatki; proračuni; oborožene sile; financiranje